UVB LED epitaxial structure based on Mg-doped AlN template and preparation method thereof
By doping Mg on the top of the AlN layer, the lattice mismatch between AlN and n-AlGaN is reduced, and the performance problems caused by UVB LEDs are solved, thereby achieving the optical performance improvement of efficient UVB LEDs.
Patent Information
- Application Number
- CN202411449823.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-03-04
AI Technical Summary
The development of UVB LEDs is hampered by the lattice mismatch between the AlN template and n-AlGaN, resulting in abnormally high penetration dislocation density and high strain levels, deteriorating device performance.
By doping Mg on the top of the AlN layer, the lattice constant of AlN is expanded, and the lattice mismatch between AlN and the top n-AlGaN contact layer is reduced, and the helical dislocation density and in-plane compression stress are reduced.
It realizes high-efficiency UVB-LED with low internal stress, improves the optical performance of UVB LEDs, and increases the optical output power by 10-15% at 100mA operating current.
Smart Images

Figure CN119562672A_ABST
Abstract
Description
Technical Field
[0001] The patent of this invention belongs to the field of semiconductor materials, and in particular relates to a UVB LED epitaxial structure based on a Mg-doped AlN template and a preparation method thereof. Background Art
[0002] Ultraviolet light-emitting diodes are widely used in various fields, such as water / air purification, gas sensing, phototherapy and plant growth lighting. The development of UVB LEDs is severely hindered by the lattice mismatch between the AlN template and n-AlGaN. The Al composition of the n-type layer is 40%-50%. This lattice mismatch leads to abnormally high threading dislocation density and high strain level, which significantly deteriorates the device performance.
[0003] Currently, heteroepitaxial growth is mainly used to grow AlN materials on substrates such as sapphire and SiC. During the heteroepitaxial growth process, the lattice mismatch difference between AlN and the substrate will induce defects and residual stress in the epitaxial layer, reduce the crystal quality of AlN, and thus affect the upper AlGaN layer. Some schemes such as substrate surface patterning have successfully reduced the threading dislocations caused by substrate lattice mismatch. However, patterning schemes usually bring new problems such as the introduction of tensile strain, which will cause mismatch dislocations, cracking and / or composition changes in thick AlGaN layers. For UVB LEDs, it is urgent to develop new growth technologies and measures that can alleviate the problems of dislocation density and strain levels. Summary of the invention
[0004] One of the purposes of the present invention is to provide a UVB LED epitaxial structure based on a Mg-doped AlN template, by doping the AlN template with Mg, so that the in-plane lattice constant of the Mg-doped AlN template is increased, the lattice mismatch and threading dislocation between the AlN template and the upper AlGaN layer are successfully improved, and a high-efficiency UVB-LED with low internal stress is developed, thereby improving the optical performance of the UVB LED.
[0005] To achieve the above objectives, the present invention adopts the following technical solutions: a UVBLED epitaxial structure based on Mg-doped AlN template, which includes from bottom to top: a flat substrate, a PVDAlN layer, an AlN high temperature layer, a Mg-doped AlN high temperature layer, an AlGaN / AlN superlattice transition layer, an n-type AlGaN layer, an Al x Ga 1-x N / A y Ga 1-y N multiple quantum well active layer, Mg-doped p-type AlGaN barrier layer, Mg-doped p-type AlGaN layer, Mg-doped p-type GaN layer.
[0006] As a further improvement of the UVB LED epitaxial structure based on the Mg-doped AlN template:
[0007] Preferably, the thickness of the AlN layer of the PVDAlN layer is 1 - 300 nm, the total thickness of the AlN high-temperature layer and the Mg-doped AlN high-temperature layer is 2000 - 3000 nm, and the thickness of the Mg-doped AlN high-temperature layer is 100 - 3000 nm.
[0008] Preferably, the flow rate of Mg introduced into the Mg-doped AlN high-temperature layer is 100 - 1000 sccm.
[0009] Preferably, the material of the flat substrate is one of sapphire, silicon, or silicon carbide.
[0010] Preferably, Al x Ga 1-x N / Al y Ga 1-y The Al x Ga 1-x N / Al y Ga 1-y N multiple quantum well active layer is prepared by alternately epitaxially growing Al x Ga 1-x N well layer and Al y Ga 1-y N barrier layer, and the emission wavelength range is 280 - 320 nm. Among them, the thickness of one Al
[0011] Another object of the present invention is to provide a method for preparing the above-mentioned UVB LED epitaxial structure based on the Mg-doped AlN template, including the following steps:
[0012] S1. Deposit PVDAlN on the flat substrate by physical vapor deposition method;
[0013] S2. Use metalorganic chemical vapor deposition equipment to continue depositing the AlN high-temperature layer and the Mg-doped AlN high-temperature layer on the PVDAlN;
[0014] S3. Deposit the AlGaN / AlN superlattice transition layer, n-type AlGaN layer, and Al x Ga 1-x N / Al y Ga 1-yN multi-quantum well active layer, Mg-doped p-type AlGaN barrier layer, Mg-doped p-type AlGaN layer and Mg-doped p-type GaN layer are then annealed in a pure nitrogen atmosphere to obtain a UVB LED epitaxial structure based on Mg-doped AlN template.
[0015] As a further improvement of the preparation method of UVB LED epitaxial structure based on Mg-doped AlN template:
[0016] Preferably, the working atmosphere of the physical vapor deposition method in step S1 is an oxygen and nitrogen mixed atmosphere.
[0017] Preferably, in step S2, the growth temperature of the AlN high temperature layer and the Mg-doped AlN high temperature layer is 1100-1350°C, the growth pressure is 30-100 mbar, ammonia, trimethylaluminum and bismuthocene magnesium are introduced as reactants, the V / III molar ratio is 500-1500, and the process time is 2-3 hours.
[0018] Preferably, in step S3, the growth temperature of the AlGaN / AlN superlattice transition layer and the n-type AlGaN layer is 1100-1350° C., and the growth pressure is 30-100 mbar;
[0019] When growing the AlGaN / AlN superlattice transition layer, hydrogen as carrier gas and ammonia, trimethylaluminum and trimethylgallium as reaction gases are introduced, the V / III molar ratio is 1500-3000, the process time is 0.3-0.7h, the Al component of AlGaN is 40-80at%, and the growth thickness is 200-400nm;
[0020] When growing the n-type AlGaN layer, hydrogen as carrier gas and ammonia, trimethylaluminum, trimethylgallium and silane as reaction gases are introduced, the V / III molar ratio is 1500-3000, the process time is 2-3h, the Al component is 40-80at%, and the Si doping concentration is 2×10 18 -8×10 18 cm -3 , the growth thickness is 1500-2500nm.
[0021] Preferably, in step S3, x Ga 1-x N / A y Ga 1-y The growth temperature of the N multi-quantum well active layer, the Mg-doped p-type AlGaN barrier layer, the Mg-doped p-type AlGaN layer and the Mg-doped p-type GaN layer is 900-1200°C, the growth pressure is 50-100 mbar, and the total process time is 0.5-1h;
[0022] Growth Al x Ga1-x N / A y Ga 1-y When the N multi-quantum well active layer is formed, ammonia, trimethylaluminum, trimethylgallium and silane are introduced as reactants, the V / III molar ratio is 1500-4000, the process time is 0.15-0.3h, the Al component is 20-50at%, and the growth thickness is 40-90nm;
[0023] When growing a Mg-doped p-type AlGaN barrier layer, ammonia, trimethylaluminum, trimethylgallium and bis(cyclopentadienyl)magnesium are introduced as reactants, the V / III molar ratio is 1500-4000, the process time is 0.15-0.3h, the Al component is 55-65at%, and the growth thickness is 20-45nm;
[0024] When growing a Mg-doped p-type AlGaN layer, ammonia, trimethylaluminum, trimethylgallium and bis(cyclopentadienyl)magnesium are introduced as reactants, the V / III molar ratio is 1500-4000, the process time is 0.1-0.2h, the Al component is 20-50at%, and the growth thickness is 30-60nm;
[0025] When growing a Mg-doped p-type GaN layer, ammonia, trimethylaluminum, trimethylgallium and bismuthocene magnesium are introduced as reactants, the V / III molar ratio is 1500-4000, the process time is 0.1-0.2h, and the growth thickness is 50-100nm.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1) The present invention provides a UVB LED epitaxial structure based on a Mg-doped AlN template. The technical route is to effectively expand the lattice constant of AlN by doping Mg on the top of the AlN layer, reduce the lattice mismatch between AlN and the top n-AlGaN contact layer, and significantly reduce the screw dislocation density in the n-AlGaN layer, so as to reduce the in-plane compressive stress. The UVB LED prepared according to the method increases the light output power (LOP) by 10-15% at an operating current of 100mA.
[0028] 2) In the method of the present invention, the lattice constant of AlN can be changed according to the doping amount of Mg, so as to adjust the stress release degree of the upper AlGaN layer. Compared with the patterned substrate, no additional tensile strain is introduced.
[0029] 3) The method of the present invention is simple, stable and highly operable. It only requires the introduction of a Mg source during the normal growth process. It is compatible with different types of substrates and processes and is suitable for industrial production.
[0030] 4) The method described in the present invention has a wide range of applications and can be applied to semiconductor devices such as ultraviolet light emitting diodes, ultraviolet photodetectors, high electron mobility transistors (HEMTs), and biodetection sensors. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 is a structural diagram of a UVB LED epitaxial structure based on a Mg-doped AlN template obtained in Example 2;
[0032] Figure 2 The XRD test graphs of the UVB LED epitaxial structure prepared in Example 1 and the UVB LED epitaxial structure based on the Mg-doped AlN template prepared in Example 2, FIG. (a) is the RSM graph of Example 1; FIG. (b) is the RSM graph of Example 2; FIG. (c) is the (002) rocking curve graph of the AlN layer in Example 1 and Example 2; FIG. (d) is the (002) rocking curve graph of the AlGaN layer in Example 1 and Example 2;
[0033] Figure 3 It is a light output power-current curve diagram of the UVB LED epitaxial structure prepared in Example 1 and the UVB LED epitaxial structure based on the Mg-doped AlN template prepared in Example 2.
[0034] The meanings of the symbols in the accompanying drawings are as follows: 1. flat substrate; 2. PVD AlN layer; 3. AlN high temperature layer; 4. Mg-doped AlN high temperature layer; 5. AlGaN / AlN superlattice transition layer; 6. n-type AlGaN layer; 7. Al x Ga 1-x N / A y Ga 1-y N multi-quantum well active layer; 8. Mg-doped p-type AlGaN barrier layer; 9. Mg-doped p-type AlGaN layer; 10. Mg-doped p-type GaN layer. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0036] Example 1
[0037] This embodiment provides a method for preparing a UVB LED epitaxial structure, which specifically includes the following steps:
[0038] (1) Using a sapphire flat substrate as a growth substrate 1, a PVDAlN layer 2 with a thickness of 15 nm is deposited by physical vapor deposition;
[0039] (2) Then, the surface was subjected to high temperature treatment using MOCVD to grow a high temperature AlN layer 3. The process temperature of MOCVD was 1200°C, the growth pressure was 50 mbar, ammonia, trimethylaluminum and bis(cyclopentadienyl)magnesium were introduced as reactants, the V / III molar ratio was 800, the process time was 2.5 h, and the growth thickness was 3000 nm.
[0040] (3) Growth of AlGaN / AlN superlattice transition layer 5, MOCVD process temperature is 1200 ° C, growth pressure is 50 mbar, carrier gas hydrogen and reaction gases ammonia, trimethylaluminum and trimethylgallium are introduced, V / III ratio is 2000, process time is 0.5 h, wherein the Al component of AlGaN is 70at%, and the growth thickness is 300nm.
[0041] (4) The n-type AlGaN layer 6 was grown at a MOCVD process temperature of 1150°C, a growth pressure of 50 mbar, a carrier gas of hydrogen and a reaction gas of ammonia, trimethylaluminum, trimethylgallium and silane, a V / III ratio of 2000, a process time of 2 h, wherein the Al component was 50 at%, and the Si doping concentration was 5×10 18 cm -3 , the growth thickness is 2000nm.
[0042] (5) Then grow Al x Ga 1-x N / A y Ga 1-y N multi-quantum well active layer 7, made of Al x Ga 1-x N well layer and Al y Ga 1-y The N barrier layer is made by alternate epitaxial growth. The process temperature of MOCVD is 1150℃, the growth pressure is 100mbar, ammonia, trimethylaluminum, trimethylgallium and silane are introduced as reactants, the V / III ratio is 1500, the process time is 0.2h, the total growth thickness is 65nm, and the emission wavelength range is 280-320nm. One period includes one quantum well and one quantum barrier, where one Al x Ga 1-x The N quantum well layer is 3nm, the Al composition is 30at%, and an Al y Ga 1-y The thickness of the N quantum barrier layer is 10 nm, the Al composition is 45 at%, and a total of 5 cycles are grown.
[0043] (6) Subsequently, a Mg-doped p-type AlGaN barrier layer 8 is grown. The MOCVD process temperature is 1150° C., the growth pressure is 100 mbar, ammonia, trimethylaluminum, trimethylgallium and dicyclopentadienyl magnesium are introduced, the V / III ratio is 1500, the process time is 0.2 h, the growth thickness is 30 nm, and the Al component is 65 at %.
[0044] (7) Subsequently, a Mg-doped p-type AlGaN layer 9 is grown, the MOCVD process temperature is 1000° C., the growth pressure is 100 mbar, ammonia, trimethylaluminum, trimethylgallium and dicyclopentadienyl magnesium are introduced as reactants, the V / III molar ratio is 2500, the process time is 0.1 h, the Al component is 20 at%, and the growth thickness is 30 nm;
[0045] (8) Finally, a Mg-doped p-type GaN layer 10 is grown. The MOCVD process temperature is 950° C., the growth pressure is 100 mbar, ammonia, trimethylaluminum, trimethylgallium and dicyclopentadienyl magnesium are introduced as reactants, the V / III molar ratio is 2000, the process time is 0.1 h, and the growth thickness is 50 nm.
[0046] (9) After the growth is completed, annealing is performed for 30 minutes in a nitrogen atmosphere, and the epitaxial process is completed to obtain a common UVB LED epitaxial structure.
[0047] Example 2
[0048] This embodiment provides a method for preparing a UVB LED epitaxial structure based on a Mg-doped AlN template. The specific steps refer to those of Embodiment 1, except that, after growing a high-temperature AlN layer 3 in step (2), a Mg-doped AlN high-temperature layer 4 is grown at high temperature, the process temperature of MOCVD is 1100°C, the growth pressure is 50 mbar, ammonia, trimethylaluminum and dicyclopentadienyl magnesium are introduced as reactants, the V / III molar ratio is 800, the process time is 2.5 h, the total thickness of the AlN high-temperature layer 3 and the Mg-doped AlN high-temperature layer 4 is 3000 nm, the AlN high-temperature layer 3 is grown to a thickness of 2000 nm, the Mg-doped AlN high-temperature layer 4 is grown to a thickness of 1000 nm, and the amount of Mg introduced is 1000 sccm. The structure is as follows: Figure 1 shown.
[0049] The epitaxial wafers prepared in Example 1 and Example 2 were subjected to XRD testing, and the results were as follows: Figure 2As shown in (a) and (b), in Example 2, after growing the high-temperature AlN layer 3 in step (2), a Mg-doped AlN high-temperature layer is grown at high temperature. After Mg doping, the lattice constant of AlN increases from 0.3107nm to 0.3113nm, indicating that the lattice at the top of the AlN template is expanded and the lattice mismatch between AlN and AlGaN is reduced. Within the expected range, Mg doping is beneficial to reducing the dislocation density in n-AlGaN and greatly alleviating the compressive stress; Figure 2 (c) is the half-height width of the AlN 002 surface of the LED epitaxial structure obtained in Example 1 and Example 2. The sample doped with Mg in Example 2 shows a slight increase in the half-width of AlN (002), indicating a slight decrease in the crystal quality; Figure 2 The AlGaN (002) half-width in (d) is significantly reduced, indicating that the crystal quality of AlGaN is significantly improved. This is mainly due to the expansion of the lattice constant on the top of AlN caused by Mg doping, thereby reducing the lattice mismatch between AlN and AlGaN.
[0050] like Figure 3 As shown, at 100 mA, the light output powers of the LED epitaxial structures prepared in Example 1 and Example 2 are 8.07 mW and 9.17 mW respectively, and the light output power of Example 2 is increased by about 13.6%, and the performance is significantly improved.
[0051] Example 3
[0052] The present embodiment provides a method for preparing a UVB LED epitaxial structure based on a Mg-doped AlN template. The specific steps are similar to those of Embodiment 1, except that, after growing the high-temperature AlN layer 3 in step (2), the Mg-doped AlN high-temperature layer 4 is grown at high temperature, the process temperature of MOCVD is 1100° C., the growth pressure is 50 mbar, ammonia, trimethylaluminum and bis(cyclopentadienyl)magnesium are introduced as reactants, the V / III molar ratio is 800, the process time is 2.5 h, the total thickness of the AlN high-temperature layer 3 and the Mg-doped AlN high-temperature layer 4 is 3000 nm, the AlN high-temperature layer 3 is grown to a thickness of 1000 nm, the Mg-doped AlN high-temperature layer 4 is grown to a thickness of 2000 nm, and the amount of Mg introduced is 1000 sccm.
[0053] Example 4
[0054] The present embodiment provides a method for preparing a UVB LED epitaxial structure based on a Mg-doped AlN template. The specific steps are referred to in Example 1, except that, after growing the high-temperature AlN layer 3 in step (2), the Mg-doped AlN high-temperature layer 4 is grown at high temperature, the process temperature of MOCVD is 1100° C., the growth pressure is 50 mbar, ammonia, trimethylaluminum and dicyclopentadienyl magnesium are introduced as reactants, the V / III molar ratio is 800, the process time is 2.5 h, the total thickness of the AlN high-temperature layer 3 and the Mg-doped AlN high-temperature layer 4 is 3000 nm, the AlN high-temperature layer 3 is grown to a thickness of 100 nm, the Mg-doped AlN high-temperature layer 4 is grown to a thickness of 2900 nm, and the amount of Mg introduced is 1000 sccm.
[0055] Compared with Example 2, Examples 3 and 4 have different thicknesses when the amount of Mg introduced into the Mg-doped AlN high-temperature layer 4 is the same. By adjusting the thickness change of the Mg-doped AlN high-temperature layer 4, the stress release of the AlN layer can be controlled, thereby adjusting the stress change of the upper layer.
[0056] Example 5
[0057] The present embodiment provides a method for preparing a UVB LED epitaxial structure based on a Mg-doped AlN template. The specific steps are referred to in Example 1, except that, after growing the high-temperature AlN layer 3 in step (2), the Mg-doped AlN high-temperature layer 4 is grown at high temperature, the process temperature of MOCVD is 1100° C., the growth pressure is 50 mbar, ammonia, trimethylaluminum and dicyclopentadienyl magnesium are introduced as reactants, the V / III molar ratio is 800, the process time is 2.5 h, the total thickness of the AlN high-temperature layer 3 and the Mg-doped AlN high-temperature layer 4 is 3000 nm, the AlN high-temperature layer 3 is grown to a thickness of 100 nm, the Mg-doped AlN high-temperature layer 4 is grown to a thickness of 2900 nm, and the amount of Mg introduced is 100 sccm.
[0058] Compared with Example 4, Example 5 adjusts the change of Mg flux of the Mg-doped AlN high-temperature layer 4 to adjust the change of lattice constant, thereby adjusting the stress change of the upper layer.
[0059] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as the scope of protection of the present invention.
Claims
1. A UVB LED epitaxial structure based on Mg-doped AlN template, characterized in that: The structure includes, from bottom to top, a flat substrate (1), a PVD AlN layer (2), an AlN high temperature layer (3), a Mg-doped AlN high temperature layer (4), an AlGaN / AlN superlattice transition layer (5), an n-type AlGaN layer (6), an Al x Ga 1-x N / A y Ga 1-y N multi-quantum well active layer (7), Mg-doped p-type AlGaN barrier layer (8), Mg-doped p-type AlGaN layer (9), and Mg-doped p-type GaN layer (10).
2. The UVB LED epitaxial structure based on Mg-doped AlN template according to claim 1, characterized in that: The thickness of the AlN layer of the PVDAlN layer (2) is 1-300nm, the total thickness of the AlN high temperature layer (3) and the Mg-doped AlN high temperature layer (4) is 2000-3000nm, wherein the thickness of the Mg-doped AlN high temperature layer (4) is 100-3000nm.
3. The UVB LED epitaxial structure based on Mg-doped AlN template according to claim 1, characterized in that: The amount of Mg introduced into the Mg-doped AlN high temperature layer (4) is 100-1000 sccm.
4. The UVB LED epitaxial structure based on Mg-doped AlN template according to claim 1, characterized in that: The material of the flat substrate (1) is one of sapphire, silicon or silicon carbide.
5. The UVB LED epitaxial structure based on Mg-doped AlN template according to claim 1, characterized in that: Al x Ga 1- x N / Al y Ga 1-y The Al x Ga 1-x N well layer and the Al y Ga 1-y N barrier layer are alternately epitaxially grown, and the emission wavelength range is 280 - 320 nm. Among them, one Al x Ga 1-x N quantum well layer is 1 - 5 nm, 25% < x < 40%, and one Al y Ga 1-y N quantum barrier layer has a thickness of 5 - 15 nm, 35% < y < 50%, and the growth is repeated for 5 - 15 cycles.
6. A method for preparing a UVB LED epitaxial structure based on a Mg-doped AlN template according to any one of claims 1 to 5, characterized in that: The steps include: S1, depositing PVDAlN (2) on a flat substrate (1) using a physical vapor deposition method; S2, using metal organic chemical vapor deposition equipment, continuing to deposit an AlN high temperature layer (3) and a Mg-doped AlN high temperature layer (4) on the PVDAlN (2); S3, depositing an AlGaN / AlN superlattice transition layer (5), an n-type AlGaN layer (6), an Al x Ga 1-x N / A y Ga 1-y N multi-quantum well active layer (7), Mg-doped p-type AlGaN barrier layer (8), Mg-doped p-type AlGaN layer (9) and Mg-doped p-type GaN layer (10), and then annealing treatment is performed in a pure nitrogen atmosphere to obtain a UVB LED epitaxial structure based on a Mg-doped AlN template.
7. The method for preparing a UVB LED epitaxial structure based on a Mg-doped AlN template according to claim 6, characterized in that: The working atmosphere of the physical vapor deposition method in step S1 is an oxygen and nitrogen mixed atmosphere.
8. The method for preparing a UVB LED epitaxial structure based on a Mg-doped AlN template according to claim 6, characterized in that: In step S2, the growth temperature of the AlN high temperature layer (3) and the Mg-doped AlN high temperature layer (4) is 1100-1350° C., the growth pressure is 30-100 mbar, ammonia, trimethylaluminum and bis(cyclopentadienyl)magnesium are introduced as reactants, the V / III molar ratio is 500-1500, and the process time is 2-3 hours.
9. The method for preparing a UVB LED epitaxial structure based on a Mg-doped AlN template according to claim 6, characterized in that: In step S3, the growth temperature of the AlGaN / AlN superlattice transition layer (5) and the n-type AlGaN layer (6) is 1100-1350° C., and the growth pressure is 30-100 mbar; When growing the AlGaN / AlN superlattice transition layer (5), hydrogen as a carrier gas and ammonia, trimethylaluminum and trimethylgallium as reaction gases are introduced, the V / III molar ratio is 1500-3000, the process time is 0.3-0.7h, the Al component of AlGaN is 40-80at%, and the growth thickness is 200-400nm; When growing the n-type AlGaN layer (6), hydrogen as a carrier gas and ammonia, trimethylaluminum, trimethylgallium and silane as reaction gases are introduced, the V / III molar ratio is 1500-3000, the process time is 2-3 hours, the Al component is 40-80at%, and the Si doping concentration is 2×10 18 -8×10 18 cm -3 , the growth thickness is 1500-2500nm.
10. The method for preparing a UVB LED epitaxial structure based on a Mg-doped AlN template according to claim 6, characterized in that: In step S3, x Ga 1-x N / A y Ga 1-y The growth temperature of the N multi-quantum well active layer (7), the Mg-doped p-type AlGaN barrier layer (8), the Mg-doped p-type AlGaN layer (9) and the Mg-doped p-type GaN layer (10) is 900-1200° C., the growth pressure is 50-100 mbar, and the total process time is 0.5-1 h; Growth Al x Ga 1-x N / A y Ga 1-y When forming an N multi-quantum well active layer (7), ammonia, trimethylaluminum, trimethylgallium and silane are introduced as reactants, the V / III molar ratio is 1500-4000, the process time is 0.15-0.3h, the Al component is 20-50at%, and the growth thickness is 40-90nm; When growing a Mg-doped p-type AlGaN barrier layer (8), ammonia, trimethylaluminum, trimethylgallium and bis(cyclopentadienyl)magnesium are introduced as reactants, the V / III molar ratio is 1500-4000, the process time is 0.15-0.3h, the Al component is 55-65at%, and the growth thickness is 20-45nm; When growing a Mg-doped p-type AlGaN layer (9), ammonia, trimethylaluminum, trimethylgallium and bis(cyclopentadienyl)magnesium are introduced as reactants, the V / III molar ratio is 1500-4000, the process time is 0.1-0.2h, the Al component is 20-50at%, and the growth thickness is 30-60nm; When growing a Mg-doped p-type GaN layer (10), ammonia, trimethylaluminum, trimethylgallium and dicyclopentadienyl magnesium are introduced as reactants, the V / III molar ratio is 1500-4000, the process time is 0.1-0.2h, and the growth thickness is 50-100nm.
Citation Information
Cited By
Double-heterojunction far UVC epitaxial structure and preparation method thereof
CN121126981A